2012
DOI: 10.4067/s0718-19572012000300021
|View full text |Cite
|
Sign up to set email alerts
|

Relevancia de fuentes nitrogenadas nuevas y regeneradas en la columna de agua en Bahía Magdalena (SO Península de Baja California), México

Abstract: Relevancia de fuentes nitrogenadas nuevas y regeneradas en la columna de agua en Bahía Magdalena (SO Península de Baja California), MéxicoAbstract.-Six bimonthly surveys during 2007 were carried out in Magdalena Bay (Mexico) during spring tide conditions. Spatiotemporal variations of temperature, salinity, nitrite, nitrate, ammonium, phosphate and chlorophyll-a were analyzed in the Bay. During spring-early summer (April-June) seawaters were colder and richer in new nutrients and chlorophyll-a than autumn and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
1
0
8
Order By: Relevance
“…In contrast, during the period of faint upwellings, from August to January, it predominates in the Transition Water and Subtropical Superficial Water zone (warmer and more saline, with lower content of nutrients)(Cervantes-Duarte et al, 2013). It is considered that the main source of nutrients is the ocean(Cervantes-Duarte et al, 2012) similar to what was reported in the lagoon of San Quintin, Baja California(Camacho-Ibar et al, 2003;Ribas-Ribas et al, 2011). However, the influence of the vegetation in the lagoon (mangroves, grass, macroalgae)…”
mentioning
confidence: 64%
“…In contrast, during the period of faint upwellings, from August to January, it predominates in the Transition Water and Subtropical Superficial Water zone (warmer and more saline, with lower content of nutrients)(Cervantes-Duarte et al, 2013). It is considered that the main source of nutrients is the ocean(Cervantes-Duarte et al, 2012) similar to what was reported in the lagoon of San Quintin, Baja California(Camacho-Ibar et al, 2003;Ribas-Ribas et al, 2011). However, the influence of the vegetation in the lagoon (mangroves, grass, macroalgae)…”
mentioning
confidence: 64%
“…La primera se registró en junio (principios de verano) con la influencia del viento dominante del NO cuando se observó agua más fría y con mayor clorofila a en la zona de la boca y exterior de la laguna (Fig. 5a y 5b) debido a las surgencias costeras, las cuales ocurren con mayor intensidad de marzo a junio (Zaytsev et al, 2003;Cervantes et al, 2012;Cervantes et al, 2013). La columna de agua se caracterizó por tener en promedio la menor temperatura (<18 o C) y mayor densidad (hasta 25.59 kg m -3 a 30 m de profundidad), así como los más altos nutrientes (hasta 20.4 µM de NID y 2.3 µM de fosfato a 30 m de profundidad) y clorofila a (3.7 mg m -3 en superficie) durante el periodo de estudio.…”
Section: Discussionunclassified
“…En este ciclo la clorofila a promedio a 30 m fue significativamente mayor que a 0 y 15 m, es decir, que la distribución de clorofila no es homogénea en la columna de agua; su distribución espacial mostró mayor concentración dentro de la laguna posiblemente como resultado del aporte de nutrientes remineralizados (Fig. 5f) (Cervantes-Duarte et al, 2012).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bahía Magdalena es una de las lagunas costeras de la Península de Baja California mejor estudiadas por su alto valor ecológico y pesquero (Félix-Uraga et al, 2007);los procesos relacionados con la dinámica de nutrientes de sus aguas han sido abordados en varios estudios (Álvarez-Borrego et al, 1975;Bizarro, 2008;Cer-vantes-Duarte et al, 2010). Los principales procesos que introducen nutrientes en Bahía Magdalena son las surgencias costeras y las corrientes de marea (Zaitsev et al, 2003(Zaitsev et al, , 2014Gómez-Gutiérrez et al, 2007;Cervantes-Duarte et al, 2012). De acuerdo con algunas investigaciones los eventos de surgencia disminuyen en intensidad por efecto de El Niño (Ohman et al, 2013), siendo el agua costera la principal fuente de nitrógeno para este tipo de lagunas costeras (Ribas-Ribas et al, 2011;Cervantes-Duarte et al, 2013).…”
Section: Introductionunclassified